Quality Analysis Satsuma Age of Threadfin Bream (Nemipterus sp) Processed Using Different Kind of Flours - Pudyastuti Anggit N; Darmanto YS; Fronthea Swastawati (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
Satsuma age is one kind of diversification product, originally characterized as a traditional food from Japan, that processed by surimi added with flour, vegetables, and spices, and then cooking by frying. The aim of this research were to evaluate the effect of different kind of flours used on gel strength and hedonic value and also to know the best kind of flour use in processing of satsuma age of threadfin bream. The experimental design that used is Randomized  Block Design.  Different treatments used was different kind of flour, namely tapioca flour , sagu flour, and garut flour. The result indicated that different kind of flour treatment gave very significant different (P<0.01) on gel strength and gave significant different (P<0.05) on value of hedonic with specificate on texture , but were not significant different on ( P>0.05) on appearance , odour , taste , and colour. The result support parameter to test bite of 7.94 for treatment tapioca flour; 7.98 for treatment sago flour; and 7.40 for treatment arrowroot flour. Folding test result of 4.30 for tapioca flour; 4.26 for sago flour ; and 3.66 for arrowroot flour. The moisture content of 40.40% for tapioca flour ; 41.91%  for sago flour; and 40.89% for arrowroot flour. Protein content of 21.53% for tapioca flour ; 21.17% for sago flour; and 21.57% for arrowroot flour. Fat content of 7.97% for tapioca flour ; 7.49% for sago flour; and 7.43% for arrowroot flour.  The ash content of 2.69% for tapioca flour; 2.66% for sago flour ; and 2.36% for arrowroot flour. Carbohidrate content of 27.93% for tapioca flour ; 27.10% for sago flour; and  27.27% for arrowroot flour. Satsuma age processed using sago flour  to was most prever based on hedonic scale and has high gel strength.   Key word :  Satsuma Age, Tapioca Flour, Sago Flour, Arrowroot Flour, Gel  Strength, Hedonic